A new species of Oxalis section Palmatifoliae (Oxalidaceae) from southern Argentina - López, Alicia (2011)
A new species of Oxalis from Santa Cruz, Argentina is described. The new species, Oxalis morronei, belongs to O. section Palmatifoliae because of its general morphology and distribution, but differs from the other species included in that section by having square leaflets with the apices deeply emarginate, the bases slightly cordate and its margin wavy and ciliate. The new species is illustrated and affinities with other members of O. section Palmatifoliae are herein explained.